FACTORS AFFECTING THE LEVEL OF CORPORATE RESILIENCE AS THE IMPACT OF THE COVID-19 PANDEMIC IN INDONESIA - Rahman, Khalilul; Bahari, Asniati (Universitas Muhammadiyah Surakarta, 2022)
This study aims to provide empirical evidence on the impact of corporate social responsibility, corporate governance, sales growth, and corporate size on corporate resilience. The purposive sampling technique obtained a sample of 44 companies registered in IDX80 as of February 2020. This study uses corporate quantitative methods with secondary data from sustainability reports and annual reports published by each corporate through the website www.idx.co.id or its official website. Data analysis in this study uses multiple linear regression analysis with IBM SPSS 25 software. The findings of this study are that partially, CSR on the topic of Environment has no significant effect on corporate resilience, but the topic of Economics and Social affect corporate resilience significantly. Corporate governance on the board of commissioners and directors has no significant effect on corporate resilience, but the board of audit committee significantly affects corporate resilience. Sales growth and corporate size significantly affect the corporate’s resilience. Then, CSR, corporate governance, sales growth, and corporate size significantly affect the corporate’s resilience.